Profil Drud Related Problems (DRPs) pada Pasien Diabetes Melitus Tipe 2 di Instalasi Rawat Jalan Rumah Sakit X Provinsi Nusa Tenggara Barat Tahun 2018 - Candra Eka Puspitasari; Baiq Sofianti Annisa; Siti Rahmatul Aini; Arfi Syamsun; Zulkarnain; Melda Putri Zakiyah (Brawijaya University, 2023)
Type 2 diabetes mellitus’s patients often receive polypharmacy therapy to prevent complications, but this has the potential effect to increase Drug Related Problems (DRPs). This study aims to evaluate the incidence of DRPs in type 2 diabetes mellitus’s patients at the Outpatient Installation of X Hospital in NTB Province in 2018. This research was conducted with a retrospective cross-sectional design with a sampling technique, namely purposive sampling. After the data is obtained, then classification of the problems and causes of DRPs is carried out based on the Pharmaceutical Care Network Europe Foundation Version 8.03 (PCNE V8.03). The results obtained 112 patients where 80 patients experienced DRPs events with a total of 224 DRPs events. The pattern of anti-diabetic use was dominated by the Biguanide group, namely Metformin (33.85%), followed by Insulin (29.75%), and Sulfonylureas (28.21%). Insulin use was dominated by Insulin Aspart (13.33%), while Sulfonylureas were dominated by Glimepiride (25.13%). Therefore, DRPs that occur sequentially are the categories of adverse drug effects that may occur (66.52%), drugs without indication (15.63%), drugs that are not appropriate according to guidelines/formularies (7.14%), symptoms or indications not treated (4.91%), the frequency of using the dose was insufficient (1.79%), the frequency of using the dose was too frequent (1.79%), the drug dose was too low (1.34%), too many drugs were prescribed for indications (0.45%) and the drug dose is too high (0.45%).